Sistem skoring hematologi Rodwell sebagai metode diagnosis awal sepsis neonatorum di Rumah Sakit dengan fasilitas terbatas: sebuah tinjauan sistematis - Anak Agung Ayu Karina Damayanti; Ketut Ngurah Alit Widiada (Intisari Sains Medis, 2020)
Background: Neonatal sepsis is a major cause of morbidity and mortality in neonates with an incidence in Indonesia at about 8.7 to 30.29%. Blood culture as the gold standard for diagnosis is not available in all health care centers. An easy, fast and inexpensive diagnostic method is needed to overcome these problems. The diagnostic method that can be used is the Rodwell hematology scoring system (HSS). It uses seven hematologic parameters obtained through a complete blood count and peripheral blood smears examination. This systematic review aims to evaluate Rodwell HSS as a method for early diagnosis of neonatal sepsis in hospitals with limited facilities.Methods: A systematic review of literature searching through the Cochrane Library, PubMed, and Google Scholar journal database was done by two reviewers. The inclusion criteria were studied about the diagnostic method for neonate's sepsis using Rodwell HSS and compared neonate's sepsis diagnostic method between Rodwell HSS and blood culture. The exclusion criteria were studies that were not published in English or Bahasa, not available in full text, and study with a case report, systematic review, or meta-analysis design.Result: The hematological scoring system has the same sensitivity as its specificity. Sensitivity range is 80-100%, specificity 60.3-90%, PPV 26-73% and NPV 92.1-100%. A score of > 4 has an AUC value of 90.2%, which shows that this diagnostic test's accuracy is excellent.Conclusion: The hematological scoring system with a score of > 4 gives the most rational and reliable results for the early diagnosis of neonatal sepsis. Due to its high sensitivity, specificity, and using simple examination, making these criteria suitable to use as a method for early diagnosis of neonatal sepsis, especially in limited health facilities hospital.  Latar belakang: Sepsis neonatorum merupakan penyebab utama morbiditas dan mortalitas pada neonatus dengan angka prevalensi di Indonesia 8,7 hingga 30,29%. Pemeriksaan baku emas untuk penegakkan diagnosis yaitu kultur darah, tidak tersedia di seluruh sentra layanan kesehatan. Sebuah metode diagnostik yang mudah, cepat dan murah diperlukan untuk mengatasi permasalahan tersebut yakni dengan sistem skoring hematologi (SSH) Rodwell. Tujuan tinjauan sistematis ini adalah mengevaluasi peran SSH Rodwell sebagai metode diagnosis dini sepsis neonatorum di rumah sakit dengan fasilitas terbatas.Metode: Tinjauan sistematis berupa penelusuran literatur dilakukan oleh dua orang peneliti melalui database jurnal Cochrane Library, PubMed dan Google Scholar menggunakan operator Boolean. Kriteria inklusinya adalah studi mengenai metode diagnosis sepsis pada neonatus menggunakan SSH Rodwell dan membandingkan antara SSH Rodwell dengan kultur darah. Sedangkan kriteria eksklusinya studi yang terpublikasi tidak dalam bahasa Inggris atau Indonesia, tidak tersedia secara full-text dan desain studi berupa laporan kasus, tinjauan sistematis atau meta analisis.Hasil: SSH Rodwell memiliki sensitivitas yang sama baiknya dengan spesifitasnya. Sensitivitas berada dalam rentang 80-100%, spesifisitas 60,3-90%, PPV 26-73% dan NPV 92,1-100%. Skor >4 memberikan nilai AUC 90,2% menunjukkan akurasi test diagnostik ini sangat baik.Kesimpulan. SSH Rodwell dengan skor >4 memberikan hasil yang paling rasional dan reliabel untuk diagnosis awal sepsis pada neonatus. Penggunaan parameter yang sederhana menjadikan pemeriksaan ini cocok diaplikasikan pada rumah sakit dengan fasilitas kesehatan terbatas.